Euthanasia and the rehabilitation of wildlife casualties in Finland: decision-making varies depending on the background education of the caregivers - White, Kati; Hänninen, Laura; Valros, Anna (Frontiers in Veterinary Science, 2023)
Caring for wildlife casualties is a common aspect of animal-protection work. The range of care options of wildlife in Finland vary from professional zoos to voluntary members of the public. There are complex ethical concerns to be considered in deciding whether an injured animal should be treated or euthanized. Differing opinions and poor communication may lead to unnecessary conflicts among caregivers. We investigated opinions behind the decision-making of caregivers related to wildlife casualties using a web-based questionnaire. We asked the respondents to rate their level of agreement with 31 statements on a seven-point Likert scale. Seventy-eight respondents were included in our analysis. Animal-related education was classified as veterinarian (n=14), other (n=18), and none (n=49). The median (IQR) levels of age and work experience were 43 (17) and 5 (9) years, respectively, regardless of educational level. The groups were tested for differences on level of agreement with the statements in Kruskall-Wallis tests (with Bonferroni-corrected pair-wise tests). Overall, the strongest disagreement was with statements proposing euthanasia on the grounds that the species was common (1 (2)), the treatment would be costly (1 (4)) or long-term (1 (4)), or there was no end-of-life-solution immediately available (1 (2)). The highest agreement was with the statement advocating not euthanizing the animal if it could easily be returned to its natural habitat (7 (0)). The respondents differed in their perceptions depending on their animal-related education. The cost and length of treatment, the prevalence of the species, and a known end-of-life solution influenced the euthanasia-related decisions of veterinarians more than of respondents in the other educational groups. Those with no animal-related education expressed the least willingness to euthanize an injured wild animal, even if it would be partly dependent on humans for the rest of its life or even if the treatment would be very stressful. We concluded that attitudes and practices related to euthanasia differ depending on the respondents’ education, and that more discussion is needed on the ethical aspects behind the decision-making. This would help to increase mutual understanding among caregivers and facilitate the development of uniform standards that would potentially benefit animal welfare.